Study of Remu River Water Quality Using Dynamic Program - Thenu, Lebrina; Karnaningroem, Nieke (IPTEK The Journal for Technology and Science, 2019)
Remu River has been being a water resource for residents in Sorong City. Development in this city lead to water quality degradation of Remu River. Existing (2016) and prediction condition of Remu River in the next 2 years were defined by the behavior of BOD, COD, Fe, and DO that proceed using a dynamic program, STELLA 9.1.3. Study area involved 6 sampling points. Simulation results showed that BOD, COD, and Fe concentrations tend to increase in the next 2 years, even BOD and COD concentrations at several sampling points was higher than water quality standard, according to Government Regulation No. 82/2001. Meanwhile, DO concentration was below the limit in 4th to 6th sampling points. Pollution control strategy was conducted by setting up three scenarios: (1) procurement of Waste Water Treatment Plant (WWTP), (2) river sediment dredging, and (3) combination of both scenario. Combination of sediment dredging and procurement of WWTP scenario estimated to reduce BOD concentration to 89.82%, COD concentration to 87.02%, and increase DO concentration to 19.07%. So that, the 3rd scenario was determined as the best strategy to improve Remu River water quality, although Fe concentration cannot be controlled as it comes from nature.